2009
DOI: 10.1053/j.gastro.2009.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Medium/High-Threshold Extrinsic Mechanosensitive Afferent Nerves to the Gastrointestinal Tract

Abstract: Background & Aims-Large distensions reliably evoke sensation from the non-inflamed, nonischemic bowel, but the specialized afferent axonal structures responsible have not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
103
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 47 publications
7
103
1
1
Order By: Relevance
“…They give rise to fine branching peri-arterial axons that are preferentially associated with arterial branch points. Importantly, they are not restricted to mesenteric vessels, but continue into the gut wall, innervating the arteries and second order arterioles in the submucosa, 92 but not finer branches or capillaries. The same afferent unit can have transduction sites on both mesenteric and submucosal vessels 92 .…”
Section: Type V: Spinal Vascular Afferentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They give rise to fine branching peri-arterial axons that are preferentially associated with arterial branch points. Importantly, they are not restricted to mesenteric vessels, but continue into the gut wall, innervating the arteries and second order arterioles in the submucosa, 92 but not finer branches or capillaries. The same afferent unit can have transduction sites on both mesenteric and submucosal vessels 92 .…”
Section: Type V: Spinal Vascular Afferentsmentioning
confidence: 99%
“…Importantly, they are not restricted to mesenteric vessels, but continue into the gut wall, innervating the arteries and second order arterioles in the submucosa, 92 but not finer branches or capillaries. The same afferent unit can have transduction sites on both mesenteric and submucosal vessels 92 . These afferents detect mechanical stimuli from mechanotransduction sites on both extramural and intramural blood vessels.…”
Section: Type V: Spinal Vascular Afferentsmentioning
confidence: 99%
“…Afferent endings are exposed to monocyte derived factors as they frequently line blood vessel walls which monocytes move through as they migrate from the blood stream into the colon (Song et al, 2009). The intestinal immune system is in a constant state of activation, and monocytes frequently migrate to the intestine in health (MacDonald et al, 2011).…”
mentioning
confidence: 99%
“…The parietal peritoneum is innervated by the neurons of the dorsal root ganglia (DRG) that supply the muscles and the skin of the abdominal wall, whereas the visceral peritoneum is innervated by not only the neurons of the vagal ganglia but also the DRG (Warwick and Williams, 1973;Tanaka et al, 2002). There are several reports about the innervation of sensory afferent fibers in the serous membrane covering the gut (Iggo, 1986;Ward et al, 2003;Song et al, 2009;Zagorodnyuk et al, 2010). Iggo (1986) reported that there are distension-sensitive C-mechanoreceptor units in the serous membrane covering the gut or in the omentum.…”
mentioning
confidence: 99%
“…Iggo (1986) reported that there are distension-sensitive C-mechanoreceptor units in the serous membrane covering the gut or in the omentum. Song et al (2009) described that mesenteric afferent mechanosensitive nerve endings correspond to varicose branching axons on mesenteric blood vessels. However, there have been few studies about the distribution and the ultrastructure of the sensory nerves supplying the parietal peritoneum.…”
mentioning
confidence: 99%